Analisa Hasil Rekomendasi Pembimbing Menggunakan Multi-Attribute Dengan Metode Weighted Product - Sucipto Sucipto (Fountain of Informatics Journal, 2017)
The development world of work is influenced by several factors such as the performance of human resources, so that each company tried to get quality employees. Improvement of human resources can be obtained from the process of field work practice in college. The field supervisor is a quality improvement factor for the students. Generally the selection of lecturers of fieldwork practice practicum is done without recommendation from students. That condition make students facing problems in field work practice. One of them is the students have difficulty adjusting to the supervisor because the characteristics of lecturers obtained from the college does not match with the required students. Therefore, a recommendation system of guidance lecturers in the field of Information System Department of X University facilitates the students to recommend lecturers according to their needs. In the recommendation process of lecturers the field work practices is conducted with the assessment of five variables. Variables obtained from lecturer performance assessment. Each of these assessments is taken into account and considered according to the needs of the students in the field. That system is made using decision support system method by multi-attribute of Weighted Product. Resulted of the analysis that has been done obtained an alternative of lecturers selected from the group of fieldwork students and the evaluation of lecturer selection by the student group. The result of the method is known that the analysis can give the recommendation of the supervisor lecturers to the student group in accordance with the highest score.